PENGARUH TATA KELOLA PERUSAHAAN, STRUKTUR MODAL, DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Nadiah Nur Azizah; Agus Purwanto (Diponegoro Journal of Accounting, 2022)
This study aims to examine the influence of corporate governance (independent commissioners, independent audit committees, external auditor quality), capital structure (market leverage, total leverage), ownership structure (management ownership, institutional ownership, and foreign ownership) on firm value (Tobin's Q).This research was conducted using secondary data management method on financial reports and annual reports on manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The research sample is 51 companies. Data analysis used multiple linear regression analysis to test the formulated hypothesis.The results show that from the three proxies of corporate governance, only the quality of external auditor which has a significant positive influence on firm value, this mean that by auditing the company using the big four KAP the presentation of the company’s financial statements is more effective and avoids misstatements and human error, while independent commissioners and independent audit committees have no influence on firm value. For the two proxies of capital structure, only market leverage which has a significant positive influence on firm value, this mean that the market assessment of the company’s equity can trigger an increase in investment and it is important for companies to prioritize funding, while total leverage does not affect firm value. For the entire ownership structure proxies namely management ownership, institutional ownership, and foreign ownership, they do not give an influence on firm value. Therefore, it is important to manage the company in order to reduce agency problems. In addition, it is important for companies to manage their funding so as to increase market valuation.